Práticas de avaliação nas escolas oficiais de 1. grau, em Manaus - Mourão, Rita Etelvina de Cassia Gomes (1978)
The purpose of this paper is to examine the evaluation practices of elementary public schools of Manaus which offer from first through fourth grades,in order to determine whether the implementation of evaluation is made according to present legal prescriptions. It is an exploratory pilot study undertaken in August-- September, 1977 in schools selected through proportional stratifeid sampling. In it were inc1uded 50% of our target population involving the principals and supervisors of the selected schools, as well as 300 teachers (chosen by their principals). Data were collected through two questionnaires (one for teachers and another for supervisors) and semistructured individual interviews with the principals of selected schools. Aiming at reducing error we detivered and collected, ourselves, the questionaires (getting a 77% return rate) and personally conducted all the interviews. Data analysis focused the following variables: training of teachers in the area of evaluation according to legal prescriptions; actual evaluation practices found in schools; kind of guidance on evaluation of learning given by supervisors to teachers; and conditions for evaluation practices offered in schools to trachers and supervisors. Result suggest that, in general, evaluation practices do not measure up to actual legal standards. Defficiency in adequate information on present evaluation theory and on it ocorresponding measurements procedures and instruments, as well as insufficiency of needed conditions for implementing evaluation in conformity with legal prescriptions, loom large as key problems.